(untitled) (Baghdad Science Journal, 2021)
The metric dimension and dominating set are the concept of graph theory that can be developed in terms of the concept and its application in graph operations. One of some concepts in graph theory that combine these two concepts is resolving dominating number. In this paper, the definition of resolving dominating number is presented again as the term dominant metric dimension. The aims of this paper are to find the dominant metric dimension of some special graphs and corona product graphs of the connected graphs and , for some special graphs . The dominant metric dimension of is denoted by and the dominant metric dimension of corona product graph G and H is denoted by .